2009
DOI: 10.1021/ef900920x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Phase Wax Deposition Experiments

Abstract: The behavior of waxy crude oils in subsea production lines has been successfully investigated in a 2 in. deposition flow loop. A North Sea waxy gas condensate was used to investigate wax deposition in turbulent single-phase flow under different temperature and flow conditions. A reliable and accurate procedure for determination of wax thickness and wax roughness from pressure drop, weight, and laser measurements has been developed. The laser technique is a new and promising method to measure the spatial distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
137
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(152 citation statements)
references
References 14 publications
11
137
0
4
Order By: Relevance
“…Hoffmann and Amundsen [15] in their earlier investigations conducted experiments to verify the reproducibility of wax deposition in this experimental rig. From their investigations, they concluded that the wax deposition in the single-phase investigations were reproducible.…”
Section: Online Wax Thickness Estimationmentioning
confidence: 99%
See 4 more Smart Citations
“…Hoffmann and Amundsen [15] in their earlier investigations conducted experiments to verify the reproducibility of wax deposition in this experimental rig. From their investigations, they concluded that the wax deposition in the single-phase investigations were reproducible.…”
Section: Online Wax Thickness Estimationmentioning
confidence: 99%
“…1). For detailed description of the experimental facility interested readers are referred to Hoffmann and Amundsen [15]. In this feasibility study only a brief description of the experimental facility is presented.…”
Section: Flow Loopmentioning
confidence: 99%
See 3 more Smart Citations